2017
DOI: 10.1109/jlt.2017.2671452
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Probabilistic Shaping for Mitigation of Nonlinearities in Optical Fiber Systems

Abstract: Abstract-In this paper, finite state machine sources (FSMSs) are used to shape quadrature amplitude modulation (QAM) for nonlinear transmission in optical fiber communication systems. The previous optimization algorithm for FSMSs is extended to cover an average power constraint, thus enabling temporal optimization with multi-amplitude constellations output, such as QAM. The optimized source results in increased received SNR and thereby increased achievable information rates (AIR)s under memoryless assumption. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…It was found that temporal properties of the QAM transmit sequence that are guaranteed to occur for short CCDM outputs yet not for long blocks lead to NLI mitigation. This effect is related to previous theoretical work on shaping for the nonlinear fiber channel predicting larger gains than for a linear channel [8] and also to temporal PS over a few time slots [9,10].…”
Section: Introductionsupporting
confidence: 57%
“…It was found that temporal properties of the QAM transmit sequence that are guaranteed to occur for short CCDM outputs yet not for long blocks lead to NLI mitigation. This effect is related to previous theoretical work on shaping for the nonlinear fiber channel predicting larger gains than for a linear channel [8] and also to temporal PS over a few time slots [9,10].…”
Section: Introductionsupporting
confidence: 57%
“…Variants of the BAA can be applied in such cases without guarantee of optimality or convergence. Examples include the experimental optimization of a mid-link OPC-based channel [26] and the simulation-based optimization for channels with memory [54] later applied to the optical fiber [27].…”
Section: Gaussian Channel Examplementioning
confidence: 99%
“…[24], [25] and references therein. Relatively recently has practical optimization using mismatched decoding principles been applied to the nonlinear optical channel [26], [22], [27], [28], [29].…”
mentioning
confidence: 99%
“…The linear impairments usually originate due to chromatic dispersion (CD), fiber loss, and polarization mode dispersion (PMD). On the other hand, the nonlinear impairments are caused by two different mechanisms: (i) inelastic scattering of photons inside the fiber (e.g., SBS and SRS nonlinearities) and (ii) changes in the refractive index of fiber core via changes in optical power intensity (e.g., FWM, SPM, and XPM nonlinearities) [11]. Out of these nonlinear effects, FWM is a third-order nonlinearity that comes into picture when two or more than two signals are propagated through the fiber.…”
Section: Concept Of Fiber Nonlinearitiesmentioning
confidence: 99%